2020
DOI: 10.1186/s40364-020-00236-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum macrophage migration inhibitory factor (MIF), adiponectin, and other adipokines as potential markers of proteinuria and renal dysfunction in lupus nephritis: a cross-sectional study

Abstract: Background To date, the association of serum macrophage migration inhibitory factor (MIF) and serum adipokines with lupus nephritis is controversial. Objective To assess the utility of serum MIF, leptin, adiponectin and resistin levels as markers of proteinuria and renal dysfunction in lupus nephritis. Methods Cross-sectional study including 196 systemic lupus erythematosus (SLE) patients and 52 healthy controls (HCs). Disease activity was assessed by Systemic Lupus Erythematosus Disease Activity Index (SL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…A recent study observed that MIF amounts were increased in the allergen-induced skin tissue of atopic dermatitis murine models, and the elevated MIF levels promoted the secretion of IL-4 and IL-5, and eosinophil recruitment in the skin (Yoshihisa et al, 2011). Gamez-Nava and colleagues found that levels of MIF were higher in the serum of lupus nephritis patients than levels of MIF in that of HCs and positively correlated with the severity of proteinuria and renal dysfunction (Gamez-Nava et al, 2020). Although MIF is known as an important pro-inflammatory cytokine, the role of MIF in AR remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study observed that MIF amounts were increased in the allergen-induced skin tissue of atopic dermatitis murine models, and the elevated MIF levels promoted the secretion of IL-4 and IL-5, and eosinophil recruitment in the skin (Yoshihisa et al, 2011). Gamez-Nava and colleagues found that levels of MIF were higher in the serum of lupus nephritis patients than levels of MIF in that of HCs and positively correlated with the severity of proteinuria and renal dysfunction (Gamez-Nava et al, 2020). Although MIF is known as an important pro-inflammatory cytokine, the role of MIF in AR remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage inhibitory factor (MIF), a T lymphocyte-derived protein, is a pleiotropic inflammatory cytokine which is expressed in various cell types, including macrophages, T lymphocyte cells, eosinophils, and neutrophils (Zhao et al, 2019a;Bilsborrow et al, 2019;Gamez-Nava et al, 2020). Accumulating evidence showed that MIF exhibited a variety of biological functions in the inflammation and immune response, and was closely involved in allergic and autoimmune diseases (Yoshihisa et al, 2011;Bozza et al, 2020;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation